Analysis of factors affecting Accounting Information System Performance - Robi Maulana M.; Alan Rusdiana; Asep Qustolani; Tania Febriani Wismajaya (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Currently, Bank Majalengka is facing challenges in optimizing the performance of its accounting information system to support operational efficiency and the preparation of accurate financial reports. Technical obstacles, such as system errors or human error, often affect the performance of accounting information systems, hindering smooth transactions and reporting. This research aims to determine the influence of Education and Training Programs, User Involvement and Personal Technical Ability at Bank Majalengka. This research uses quantitative descriptive. The population in this research is employees of Bank Majalengka. The research sample was determined using a non-probability sampling technique with a purposive sampling method. Aims to obtain samples that match the research criteria. The sample used was 48 Bank Majalengka employees who used an accounting information system. The analytical method used in this research is multiple regression analysis with the help of SPSS version 26 software. The results of this research show that Education and Training Programs and Personal Technical Capabilities have a significant effect on Accounting Information System Performance. Meanwhile, user involvement does not have a significant effect on the performance of the accounting information system.